Sette scritti politici liberi - Kant, Immanuel (Firenze University Press, 2011)
At the end of the eighteenth century, before and during the French Revolution, Kant wrote intensively about politics. This book brings together the translations of his principal philosophical-political works, with the editor's annotations, from the essay on Enlightenment through to the writing on progress. The texts are subject to a Creative Commons licence, so that they can be amended without restrictions, retaining the same rights. Open access publication alone can achieve freedom in the public use of reason. The decision to free a classic work from economic monopoly and censure is intended to demonstrate that open access is not an academic theory but a reality that can give value and meaning to the establishment of a public university. Making Kant read means much more than merely reading him.